Pengaruh Ukuran Perusahaan Dan Kepemilikan Institusional Terhadap Financial Distress - Apriani, Dini; Ritonga, Ferdiansyah (Politeknik Negeri Ambon, 2024)
Financial distress is a stage of decline in financial condition that occurs before bankruptcy or liquidation. Bankruptcy is a problem that companies should be aware of. This study aims to analyze the relationship between company size and institutional ownership of Financial Distress in manufacturing companies in the transportation and logistics sector listed on the Indonesia Stock Exchange for the period 2018 - 2022. The research method used in this research is the quantitative method. The population used in the study was 36 companies while the sample used in the study was 25 companies with the sampling method, namely purposive sampling. The data analysis technique used is multiple linear regression. The results of this study concluded that company size and institutional ownership have a negative and significant effect on financial distress.